Kurdish diaspora mobilisation in Denmark supporting the struggle in Syria - Schøtt, Anne Sofie (Edinburgh studies on diasporas and transnationalism, 2021)
Anne Sofie Schøtt explores how the Kurdish diaspora in Denmark supported the Kurdish struggle in Syria from the battle of Kobane (2014) to the defeat in Afrin (2018). She examines the political lobbyism, the courtroom activism and the humanitarian action of the various Kurdish diaspora groups.